Database construction for Vietnamese catfish genome - Vu, Nguyen Hoang; Phuong, Nguyen Thanh; Binh, Le Thi Nguyen; Oanh, Kim Thi Phuong (Vietnam Journal of Biotechnology, 2020)
Molecular biological research plays an important role in aquaculture, contributes to the improvement of broodstocks efficiently. Recently, with the development of next-generation sequencing (NGS) technology, genomic studies have been rapidly increased, in which data organisation and management hold a crucial position. After obtaining NGS sequencing data of Vietnamese catfish (Pangasianodon hypophthalmus), we have analysed and annotated the catfish genome, from which we have constructed a database for efficient usage. The database is built upon open source software following a three-layer model (interface, Web service and database) with a convenient interface through Web browsers. Users can look up sequence and annotation data as well as visualize sequences through the Jbrowse genome browser. This database is important resource for functional genome and genetic improvement of the catfish.